ADAPTASI MASYARAKAT PALEMBANG DI TANJUNG BALAI KARIMUN - Fajrina, Adlia; ", H. M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Adaptation is individual self adjustment process in an environement to be accepted in thesociety. So that adaptation is an important thing to do. Many of the migrants came to a newplaces and succed in their adaptation. However, some of the migrants failed in doing theiradaptation in case of the process of the adaptation. Many migrants in Tanjung Balai Karimuncame from Palembang. This study is aim to give an overview of how the characteristic and theadaptation of Palembang migrants in term social, economy and in Tanjung Balai Karimun. inwhich they already becaming the part of the society in their environment as the basic indicatorsin this case. The method used is descriptive quantitative. Observation technique andquestionnaire are the way to find out the result. As the way of taking sample which used quotasampling technique is set up the quota 15 people from each organization so the amount is 30peeople in condition already settled minimal for 5 years in Tanjung Balai Karimun. Theory usedfor this study are Structural Functional and the books is migrant, adaptation, and socialnetwork. The result of this study shows that Palembang And all the respondence in this study isPalembang society which succed in their adaptation in terms of sosial, economy and culture. Inwhich they already becaming the part of the society in their environment as the basic indicatorsin this case.Keyword: Adaptation, Characterisctics, Society